Estimation of Uplift Pressure Equation at Key Points under Floor of Hydraulic Structures. Issue 1 (1st January 2021) - Hamid Rasool, Mohammed; Al-Maliki, Laheab A.; Al-Mamoori, Sohaib Kareem; Al-Ansari, Nadhir
Abstract: Most of the hydraulic structures rest on an impervious foundation to reserve water at the upstream side. The water heads difference leads to water movement from the higher to the lower head through the porous soil layer beneath the foundation, generating an uplift pressure under the structure floor. In this study, a new method is presented to estimate the uplift pressures at key points by performing sub-surface flow analysis using the Analysis SYStem (ANSYS) software. Then a statistical analysis to validate the proposed equations is conducted using the SPSS software. The case study for this research is a barrage in Kufa city-Iraq. The used data to implement this study was water levels, soil permeability, and length of imperious foundation. The obtained results show good outcomes from using the proposed method to develop uplift pressure equations. The comparison of the current study results with Khosla's equation showed good agreement where the coefficient of determination ( R 2 ) and the standard error of estimation (SEE) for the equations were between (99.9–97.8) and (0.024–0.11), respectively.